Income smoothing practices and empirical testing using discretionary accounting changes - Theresia Trisanti (Journal of Economics, Business, and Accountancy Ventura, 2014)
Financial statements of listed firms are analyzed by financial analysts and investors. In this case, the firms may suffer from stock price declines if they do not meet market expectations. Listed firms may not only have incentives to avoid income declines and losses, they also have incentives to meet or beat market expectations in order to pre- vent declines in stock price. Income smoothing (IS) is the intentional dampening of fluctuations about some levels of income that is considered to be normal for a firm. IS manipulation has a clear objective, which is to produce a steadily growing stream of income. In this study, income-smoothing practices of Indonesian listed companies are detected through empirical tests using discretionary accounting changes (DAC) as IS instrument. Sample firms are classified as smoothers and non-smoothers using income smoothing behavior index. Results show that possible motivations of DAC transac- tions are income smoothing. The two independent variables such as external audit quality institutional ownership have significant influence towards IS practices. But, the type of industry has no significant relationship towards IS Practices.